Limb-Specific Comparison of Flow-Mediated Dilation in Abdominal Obese Pre-menopausal Women - Robert M. Restaino; Matthew A. Barlow (Artery Research)
Abstract Purpose Normal aging can lead to arterial wall stiffening and development of atherosclerosis; however, the effects of overweight conditions can expedite the dysfunction of arterial health. In an earlier study, we identified in a group of abdominal obese pre-menopausal woman that during menses, these women had decreased vascular conductance of the brachial artery during dynamic hand-grip exercise. Endothelial function in abdominal obese (AO) premenopausal women could be associated with being highly sedentary which attenuates dilatory responses to FMD of both upper and lower limb vascular function. We hypothesized that the AO women would exhibit limb-specific differences in artery dilation with reduced dilation in the popliteal artery as compared to the brachial artery. Methods Artery dilatory responses in the brachial and popliteal arteries were assessed using flow-mediated dilation (FMD) in age-matched sedentary controls and AO groups during menses. Results Significant differences were found between groups including % BF, BMI, weight, waist to hip ratio, fasting blood glucose, and oxLDL. A between-group comparison revealed significantly lower percent dilation of the popliteal artery in AO participants compared to controls (p < 0.05) not present in the brachial arteries. Our results also indicate a difference in the time-to-peak (TP) of dilation between the control (33.38 ± 3.232) and AO (62.104 ± 5.813) groups (p < 0.01). Following FMD correction with shear rate as the covariate, significant differences in FMD between the brachial and popliteal artery were abolished. Conclusion We conclude that young, AO women show a limb-specific difference in dilation of the upper and lower extremities when compared to controls. Thus, reductions in FMD of the popliteal artery could be due to impaired dilation of the downstream resistance vasculature preventing increases in shear within the leg conduit arteries not as significantly in the arms.